Vertical and Regional Integration to Promote African Textiles and Clothing Exports : A Close Knit Family? - World Bank (Washington, DC, 2012)
Apparel production is especially labor intensive, with low start-up investments and easily transferable technology. Furthermore, the labor requirements can be easily met with low and semi-skilled workers, especially women. As a result, many countries with competitive labor costs, especially in South and East Asia, have captured significant shares in the world market during the last four decades. Despite the potential development benefits and their various sources of comparative advantage, few African countries have managed to establish a presence in the global textiles and apparel markets until recently. As a result, Africa as a whole remains a net importer of textiles and clothing even though it is a net exporter of cotton. The future of apparel exporters in sub-Saharan Africa is, however, rather uncertain as they face two major challenges for their products: i) increased competition from large, low-wage producers such as India, China, Bangladesh and Pakistan following the phase-out of quotas after the expiry of the ATC; and, ii) the expiration of the third-country fabric derogation under AGOA scheduled for 2013. This study explores the potential for regional and vertical integration to overcome these challenges and identifies obstacles to this. Timing is important since both the EU and the US have recently imposed trade restrictions on China (until 2008) to protect their domestic textiles and clothing industries. These safeguards provide a brief opportunity for sub-Saharan African producers to integrate their textiles and clothing industries both domestically and regionally.